Reflections on contemporary values, beliefs and behaviours : the adventures of an enquiring mind - Gautam, Prasanna Chandra, 1945- (Cambridge Scholars Publishing, 2018)
"This book is a unique presentation of common but highly important issues that affect us all deeply. These are illustrated with personal anecdotes to which the readers can relate and compare with their own experiences in life. Each chapter is independent and presented in a conversational manner which makes reading easy. The book deals with a wide range of subjects, such as sex and sexuality, euthanasia, self-confidence, superstition, religion, evolution, parenting, conflicts, leadership, and the interpretation of scriptures, among others. In addition to presenting the essence of many philosophical concepts and contrasting them with scientific evidence, the book asserts that our world has never before been richer and more technically advanced, but that our unthinking brains have precipitated unhappiness, conflicts, poverty, greed, crime and selfishness. A book of huge interest generally, this is also useful as a handy source of information for the students of humanities, the linguists and translators of ancient languages."--